Gene therapy ameliorates neuromuscular pathology in CLN3 disease - Ewa A. Ziółkowska; Albina Jablonka-Shariff; Letitia L. Williams; Matthew J. Jansen; Sophie H. Wang; Elizabeth M. Eultgen; Matthew D. Wood; Daniel A. Hunter; Jaiprakash Sharma; Marco Sardiello; Robyn Reese; Alan Pestronk; et al. (Acta Neuropathologica Communications)
Abstract CLN3 disease is a neuronopathic lysosomal storage disorder that severely impacts the central nervous system (CNS) while also inducing notable peripheral neuromuscular symptoms. Although considerable attention has been directed towards the neurodegenerative consequences within the CNS, the involvement of peripheral tissues, including skeletal muscles and their innervation, has been largely neglected. We hypothesized that, CLN3 deficiency could directly influence peripheral nerves and investigated the neuromuscular system in Cln3 Δex7/8 mice. Our study found no overt loss of sciatic nerve axons or demyelination in 18-month-old Cln3 Δex7/8 mice at disease endstage, but a marked reduction of terminal Schwann cells (tSCs) at lower limb neuromuscular junctions (NMJs), culminating in progressive denervation of these NMJs which appeared abnormal. This led us to investigate skeletal muscle where we found significant myofiber atrophy and decreased and misplaced myofibril nuclei. Similar myopathic alterations were present in a muscle biopsy from an 8-year-old human CLN3 patient shortly after diagnosis. To assess a potential therapeutic intervention, we administered intravenous gene therapy using AAV9.hCLN3 to neonatal Cln3 Δex7/8 mice, which at disease endstage, entirely prevented tSC loss and NMJ abnormalities, while also averting skeletal muscle atrophy. These findings underscore the underappreciated, yet substantial effects of CLN3 disease beyond the CNS, highlighting peripheral neuromuscular pathologies as novel features of this disorder. Our findings also indicate that these manifestations could be amenable to treatment via gene therapy, opening new therapeutic strategies in the management of CLN3 disease.